Assessment of electrocardiographic parameters in adult patients undergoing extracorporeal shockwave lithotripsy - Gündüz Durmuş; Muhsin Kalyoncuoğlu; Mehmet Baran Karataş; Yiğit Çanga; Semi Öztürk; Ender Özal; Yasin Çakıllı; Tuncay Kırış; Barış Güngör; Ahmet Taha Alper; Mehmet Mustafa Can; Osman Bolca (KARE Publishing, 2017)
Objective: Extracorporeal shock wave lithotripsy (ESWL) is a safe and effective treatment for urinary tract calculi. While serious side effects are rare, transient cardiac arrhythmias may occur. New electrocardiographic (ECG) parameters, such as P wave dispersion (PWD), QT dispersion (QTd), T peak to T end (Tp-e) interval, Tp-e interval/QT ratio, and Tp-e interval/corrected QT ratio have been defined to help predict atrial and ventricular arrhythmias. However, effect of ESWL on these ECG parameters has not been previously investigated. The present study was an examination of the effect of ESWL on ECG parameters. Methods: Total of 40 consecutive patients who underwent ESWL were prospectively enrolled in the study. Pre-procedure ECG parameters were compared with post-procedure ECG parameters. Results: PWD values were significantly longer on post-procedure ECG compared with pre-procedure ECG (p=0.017). Corrected QT duration and QTd were significantly longer on post-procedure ECG compared with pre-procedure ECG (p=0.046 and p=0.008, respectively). In addition, Tp-e interval, Tp-e interval/QT ratio, and Tp-e interval/QTc ratio were significantly longer post procedure (p=0.035, p=0.045, and p=0.022, respectively). In univariate correlation analysis, duration of procedure was significantly correlated with post-procedure PWD, QTc, and QTD values. Conclusion: Clinical use of ECG parameters may be helpful in monitoring of patients receiving ungated ESWL in order to detect cardiac dysrhythmia.